Introduction to the special section on computer-based assessment of cross-curricular skills and processes - Greiff, Samuel; Martin, Romain; Spinath, Birgit (Journal of educational psychology, 2014)
This article introduces the special section on computer-based assessment of cross-curricular skills and processes. It presents a collection of articles that were submitted to Journal of Educational Psychology in response to a call for papers on this topic. This special section includes six articles that report cutting-edge research and present a cross-section of different topics. (PsycINFO Database Record (c) 2019 APA, all rights reserved)